Advances in selective hydrogenation of nitrobenzene toward p-aminophenol - Jinzhi Lu; Hao Wang; Xiao Cai; Yan Zhu (Sustainable Chemistry for Climate Action)
p-Aminophenol is an important intermediate for dyestuff, medical and rubber. Selective hydrogenation of nitrobenzene is a green and environmentally friendly preparation process for the p-aminophenol synthesis. In this review, we first introduce the catalytic performances of a series of catalysts for the selective hydrogenation of nitrobenzene to p-aminophenol. Then the typical reaction pathways of nitrobenzene hydrogenation toward p-aminophenol are proposed. Moreover, various acid reaction systems that can replace sulfuric acid are described. Finally, the existential problems of this reaction and future efforts are pointed out. It is anticipated that the review can provide perspectives on the design rules of highly active and highly selective catalysts for the selective hydrogenation of nitrobenzene to p-aminophenol.